Optimization of cutting parameters of sugar palm fiber- reinforced unsaturated polyester composite with laser beam and abrasive water jet cutting technologies - Masoud, Fathi Aluhishi Muftah (2023)
This study aims to investigate unconventional techniques for cutting a natural fiber reinforced polymer composite as alternative approaches to traditional cutting methods. Due to the cutting forces associated the conventional cutting methods and the heterogeneous nature of natural fiber composites, number of defects appear with utilizing the traditional cutting techniques, such as, poor surface quality, material damage, delamination, fiber fraying and dimensional instability. Overcoming these defects is the primary motivation for conducting this study. Taking all these aspects into account, the study formulates an investigation of laser (LBM) and abrasive water jet (AWJ) machining techniques utilized to cut sugar palm fiber reinforced unsaturated polyester (SPF- UPE). The goal is to optimize the input parameters that control the quality of the output parameters and to assess the suitability of both cutting technologies for the composite material under study. In laser beam cutting technique, the laser power, traverse nozzle speed, and assist gas pressure were selected as the input variable parameters, meanwhile the operating water pressure, traverse nozzle speed, and stand-off-distance (SOD) were chosen as input variable parameters in abrasive water jet cutting technique. Dimensional stability, surface quality, and kerf taper angle were the optimized output responses in both cutting techniques, as well as heat affected zone (HAZ) in laser beam cutting process. Taguchi’s approach was used to estimate the optimum levels of the input parameters and their significance. Analysis of variation (ANOVA) was utilized to determine the contribution of every single input parameter. What is new in this study is the testing of a broad range of the input parameters values on three different material thicknesses, unlike most of the previous studies in the field that tested limited values of the input parameters with one material thickness. Both of cutting process have been made successfully and good cutting quality can be achieved. The best cutting quality in laser beam cutting process was recorded with applying laser power ranging from 200 to 400W, and traverse speed ranging from 150 to 250 mm/min for 2 mm plate thickness. The optimum parameter range was between 1000 to 1600W laser power with traverse speed ranging from 5600 to 6000 mm/min for 4 mm plate thickness, while the optimum range of input parameters in the case 6 mm thickness ranged from 2000 to 2600W laser power and 7600 to 8000 mm/min traverse speed. In the abrasive water jet cutting process, the best results were recorded at water pressure ranging from 300 to 340 bar in all cases of material thickness with corresponding traverse nozzle speeds ranging from 2400 to 2800 mm/min for 2 mm plate thickness, 1800 to 2200 mm/min for 4 mm plate thickness, and 1200 to 1600 mm/min for 6 mm plate thickness. The experimental results of the study provide practical data for the cutting of SPF-UPE composites with AWJ and CO2 laser machining technologies.